A Retrospective Review of Ambulatory Oral and Maxillofacial Surgery in a Suburban Tertiary Hospital in Nigeria - Famurewa, Bamidele A.; Jimoh, Taoheed A.; Ugwu, Ethelbert I.; Oginni, Fadekemi O. (Libyan International Medical University Journal, 2024)
Background Ambulatory surgical procedures are integral aspects of oral and maxillofacial surgical (OMS) practice.Objective The aim of this study is to report the scope of ambulatory OMS procedures in a Nigerian suburban teaching hospital.Method A retrospective review of ambulatory OMS procedures performed at Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria, between March 2021 and February 2022 was conducted. Sociodemographic data, diagnoses, procedures, type of anesthesia, and immediate postoperative complications were retrieved from patients' records. Data were analyzed using the Statistical Package of Social Sciences (SPSS) version 22.Results Two hundred and fifty-two ambulatory OMS procedures were performed during the 12-month study period. This accounted for 80.3% (252/314) of elective surgeries. The patients' mean (standard deviation [SD]) age was 32.2 (10.4) years, while a slight male preponderance (51.6%) was recorded. Third molar surgery was the commonest (48.0%) procedure undertaken in ambulatory setting. Most (90.9%) of them were performed under local anesthesia. Satisfactory postoperative pain control was achieved with the use of oral nonsteroidal anti-inflammatory analgesics in most patients (81.7%). However, owing to a failed ambulatory session, there was an eventual admission rate of 0.4% (1/252).Conclusion Ambulatory surgical procedures constitute the majority of the OMS elective cases, with third molar surgery being the commonest procedure. Judicious prescription and administration of oral analgesics were effective in managing postoperative pain in our day case OMS patients. We recommend a prospective study to determine an intermediate/long-term outcome of care in ambulatory settings.
Keywords: day case surgery; local anesthesia; oral and maxillofacial day surgery; outpatient surgery